DECISION SUPPORT FRAMEWORK FOR SUSTAINABLE SELECTION OF EARTHMOVING EQUIPMENT IN THE MALAYSIAN CONSTRUCTION INDUSTRY - ALI KHAN, MUHAMMAD WARIS (2015)
Onsite mechanization in construction is characterized by the usage of equipment, machineries and non-road vehicles. The utilization of heavy equipment increases construction productivity as well as reduces the dependency on intensive labor. Among the various types of construction equipment, earthmoving equipment are considered as of paramount interest for heavy construction activities due to their cost impact, operational intricacy. and productivity. During the construction phase, selection of appropriate earthmoving equipment has been a key factor in the success of many construction project. This decision is typically made by considering financial and non-financial factors such as cost, equipment productivity, capacity and quality.